Paternal uniparental disomy for chromosome 14: prenatal management - Silva, Joana Isabel Igreja da (2019)
We present a case of a 34-year-old multiparous woman who had been diagnosed with a 14 weeks' gestation showing an abdominal wall bulge possibly representing an omphalocele, containing liver and intestinal loops, at her first-trimester ultrasound scan. At 16 weeks' gestation, an amniocentesis was performed and karyotype analysis revealed a balanced Robertsonian translocation between chromosomes 13 and 14 in a female fetus (45,XX,der(13;14)(q10;q10)). Given this result and ultrasound findings, karyotype and molecular study of the couple were suggested. The results pointed out the absence of maternal contribution to the analysed regions by paternal uniparental disomy for chromosome 14 (isodisomy), which is associated with a severe phenotype. The correlation between ultrasound findings and the genetic study is primordial to guide the diagnostic assessment and to establish the prognosis of the fetal pathology.